Nursing dress code and perception of a nurse by patients - Pawłowski, Piotr; Mazurek, Paulina; Zych, Magdalena; Zuń, Katarzyna; Dobrowolska, Beata (Nursing in the 21st Century, 2019)
NURSING DRESS CODE AND PERCEPTION OF A NURSE BY PATIENTSIntroduction. Professional image of the nurse in the opinion of the patient community is conditioned by many variables, including professional attire. A worthy representation of the nurse profession is the responsibility of all those who care for the patient. Aim. Determining the impact of dress code on shaping the professional image of nurses in the opinion of patients. Material and methods. Non-systematic review method of the literature available. The data was obtained by searching online databases, such as: Google Scholar, PubMed, CINAHL Complete as well as electronic resources of nursing magazines.Results. In the perception of hospitalized patients, the nursing dress code affects the level of trust in those who care for patients, it also constitutes an important element in assessing their professionalism, knowledge or confidence when performing specific medical interventions. Adapted to the needs, a suitably selected style of professional attire of a nurse employed in a given health care facility enables her proper identification of them against the background of other members of the therapeutic team or administrative employees. In addition, the comfort of nurses is a significant factor for patients in dress code strategy planning; it often determines professionalism and quality of services provided.Conclusions. There is a relationship between the external appearance of nurses and their professional image and the patients’ perception of their professional skills as well as the level of their professionalism. Dress code in a health care facility may constitute a significant element of image policy for both a health care facility itself and a group of nurses.